Cytotoxicity and biocompatibility of a new bioceramic endodontic sealer containing calcium hydroxide - Francine Benetti; Índia Olinta de Azevedo Queiroz; Pedro Henrique Chaves de Oliveira; Leticia Citelli Conti; Mariane Maffei Azuma; Sandra Helena Penha de Oliveira; Luciano Tavares Angelo Cintra
Abstract: This study evaluated the cytotoxicity and biocompatibility of a new bioceramic endodontic sealer (i.e., Sealer Plus BC) in comparison with those of MTA Fillapex and AH Plus. L929 fibroblasts were cultured and Alamar Blue was used to evaluate cell viability of diluted extracts (1:50, 1:100, and 1:200) from each sealer at 24 h. Polyethylene tubes that were filled with material or empty (as a control) were implanted in the subcutaneous tissue of rats. The rats were killed after 7 and 30 d (n = 8), and the tubes were removed for histological analysis. Parametric data was analyzed using a one-way ANOVA test, and nonparametric data was analyzed via the Kruskal-Wallis test followed by the Dunn test (p < 0.05). A reduction in cell viability was observed in the extracts that were more diluted for Sealer Plus BC when compared to that of Control and AH Plus (p < 0.05). However, the 1:50 dilution of the Sealer Plus BC was similar to that of the Control (p > 0.05). Conversely, more diluted extracts of MTA Fillapex (1:200) and AH Plus (1:100 and 1:200) were similar to the Control (p > 0.05). Histological analysis performed at 7 d did not indicate any significant difference between tissue response for all materials, and the fibrous capsule was thick (p > 0.05). At 30 d, Sealer Plus BC was similar to the Control (p > 0.05) and MTA Fillapex and AH Plus exhibited greater inflammation than the Control (p < 0.05). The fibrous capsule was thin for the Control and for most specimens of Sealer Plus BC and AH Plus. Thus, Sealer Plus BC is biocompatible when compared to MTA Fillapex and AH Plus, and it is less cytotoxic when less-diluted extracts are used.